Paper-based methodology for investigation of triboelectric nanogenerators. (November 2019) - Zhu, Zhiyuan; Fu, Jiangmin; Xia, Kequan; lu, Jianguo; Zhang, Hongze; Lou, Haijun; Xu, Zhiwei
Abstract: Triboelectric nanogenerators (TENGs) have been investigated as a promising methodology to harvest mechanical energy into electricity. The matching impedance and the transient property of TENGs are important for their practical application. In this work, we proposed novel paper-based methodology for investigation of TENGs. First, we propose a novel method for triggering transience of pencil-on-paper (POP)-TENGs using household microwave oven and commercial graphite pencil. Moreover, a fast, simple and cost-effective approach for measuring the matching impedance of TENG based on paper variable resistor is proposed. The results of this work are beneficial for simple, fast and cost-effective functionalization of TENGs.